2023
DOI: 10.3390/foods12071443
|View full text |Cite
|
Sign up to set email alerts
|

Cefotaxime-, Ciprofloxacin-, and Extensively Drug-Resistant Escherichia coli O157:H7 and O55:H7 in Camel Meat

Abstract: The present study aimed to explore for the first time the occurrence and the antimicrobial resistance profiles of E. coli O157:H7 and O55:H7 isolates in camel meat in Egypt. Among the 110 camel meat samples examined using standardized microbiological techniques, 10 (9.1%) and 32 (29.1%) were positive for E. coli O157:H7 and E. coli O55:H7, respectively. In total, 24 isolates were verified as E. coli O157:H7, while 102 isolates were confirmed serologically as E. coli O55:H7. Multiplex PCR revealed the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In Egypt, E. coli O26, O86, O111, O124, and O128 were isolated from camel meat slaughtered in Elbagour, Menouf, and Shibin Elkom slaughter houses at a prevalence rate of 30%, 20%, and 15%, respectively ( Edris et al ., 2013 ). Multidrug-resistant E. coli was also isolated from camel meat in Mansoura city ( Sallam et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, E. coli O26, O86, O111, O124, and O128 were isolated from camel meat slaughtered in Elbagour, Menouf, and Shibin Elkom slaughter houses at a prevalence rate of 30%, 20%, and 15%, respectively ( Edris et al ., 2013 ). Multidrug-resistant E. coli was also isolated from camel meat in Mansoura city ( Sallam et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Khalid et al 20 study in Egypt from the period of November 2021 to March 2022 reported that meat marketed in Beheira Governorate, Egypt, was contaminated with multi and extensively drug resistant Shiga toxigenic E. coli O157:H7 with a prevalence rate 9.1%; 10 out of 110 testes samples.…”
Section: Discussionmentioning
confidence: 99%
“…The inconvenience of E. coli has been widely reported. Sallam and collaborators [40] highlighted that camel meat may be a vehicle for multi-and extensively drug-resistant E. coli. No Listeria monocytogenes were detected, as Bader and collaborators deduced in dry camel meat [5].…”
Section: Microbiological Changementioning
confidence: 99%